An analysis and exposition of form in the discipline of easel painting - van der Merwe, Vivian Hubert (Michaelis School of Fine Art, 2023)
The text of this volume is intended to introduce the reader to the cycle of paintings submitted for the Master of Fine Art degree. The very nature of form imposes severe limitations on any kind of semantic or linguistic recourse to the visual form of painting, and this has been the cardinal difficulty in drawing together the verbal and visual elements of my research. At best, the text and reproduction of the works can be seen in juxtaposition. The first two chapters, "The Genesis of Form" and "Form and Silence" constitute the conceptual background to the field of enquiry. The third chapter "The Work" deals with the specific concerns and categories of form which pertain to the cycle of paintings. This is followed by "The Conclusion" which serves as a brief and personal appraisal of the work. The text and illustrations have been separated to permit undivided perusal of the paintings.